Sneak Path Free Reconfiguration of Via-switch Crossbars Based FPGA - Doi, Ryutaro; Yu, Jaehoon; Hashimoto, Masanori (2018 IEEE/ACM International Conference on Computer-Aided Design (ICCAD), 2018)
FPGA that utilizes via-switches, which are a kind of nonvolatile resistive RAMs, for crossbar implementation is attracting attention due to higher integration density and performance. However, programming via-switches arbitrarily in a crossbar is not trivial since a programming current must be provided through signal wires that are shared by multiple via-switches. Consequently, depending on the previous programming status in sequential programming, unintentional switch programming may occur due to signal detour, which is called sneak path problem. This problem interferes the reconfiguration of via-switch FPGA, and hence countermeasures for sneak path problem are indispensable. This paper identifies the circuit status that causes sneak path problem and proposes a sneak path avoidance method that gives sneak path free programming order of via-switches in a crossbar. We prove that sneak path free programming order necessarily exists for arbitrary on-off patterns in a crossbar as long as no loops exist, and also validate the proof and the proposed method with simulation-based evaluation. Thanks to the proposed method, any practical configurations of via-switch FPGA can be successfully programmed without sneak path problem.